PERENCANAAN PENGAJARAN - Nasution, Asmadawati (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
AbstractOne step needed by a professional teahcer is to design of lesson plan. It can motivate teacher readier efectively and efissiontly. Teaching must be related to the prinsip of the design in order to change the students’ behaviors.Keywords: Design and Teaching